The role of communication and creativity in the implementation of sustainability and sustainable innovations - Atkočiūnienė, Zenona Ona; Siudikienė, Daiva; Girnienė, Ingrida (Creativity Studies, 2024)
Sustainable development becomes a strategic goal of modern business organizations and an aspiration to ensure long-term economic growth through the creation of innovative products and services, saving resources and their sustainable use, nurturing the environment, and contributing to the creation of public welfare. It should be noted that communication and creativity constitutes a significant part of the innovation generation and implementation process. Promotion of idea generation, the interpretation of the need for innovation, the provision of opportunities for expressing new ideas, the development of relationships both within the team itself and with stakeholders are important in each phase of communication. The article presents the research, the purpose of which is to determine how creative communication solutions condition the involvement of the organization’s stakeholders, developing sustainability and creating sustainable innovations in Lithuanian business organizations. The applied research method is qualitative content analysis of the web pages of the largest Lithuanian business organizations, seeking to collect data on the essential organization of sustainable innovation development activities, challenges and features of stakeholder involvement. The data required for the research was collected by reviewing the publicly available information of 100 websites of Lithuanian business organizations in order to determine the essential communicated sustainability topics. Documents related to sustainable activities of organizations were also investigated (sustainability performance reports, corporate social responsibility reports, etc.). The results of the study show that Lithuanian business organizations consider the development of a sustainable activity strategy an important priority in the near term. However, although they understand the need for sustainable activities, developing sustainable innovations by involving stakeholders in these activities is difficult due to the lack of such practices and various organizational factors.